Mentoring at minority serving institutions : theory, design, practice and impact - McClinton, Jeton; Mitchell, David S. B.; Carr, Tyrell; Melton, Mark A.; Hughes, Gerunda B. (Perspectives in mentoring., 2018)
"The primary thrust of the proposed volume is to provide information for higher education minority serving institutions (MSIs) and other institutions and individuals interested in providing and/or improving mentoring programs and services to a variety of target groups. The editors are interested in how mentorship can produce beneficial outcomes for the mentor that may be similar to or different from outcomes in other educational contexts. Thus, the purpose of this volume is to showcase, through case studies and other forms of empirical research, how successful mentoring programs and relationships at MSIs have been designed and implemented. Additionally, we will examine the various definitions and slight variations of the meaning of the construct of mentoring within the MSI context. It is our intent to share aspects of mentoring programs and relationships as well as their outcomes that have heretofore been underrepresented and underreported in the research literature" --